Recent Advances and Future Prospects of Aggregation‐induced Emission Carbohydrate Polymers. Issue 10 (7th March 2017) - Liu, Meiying; Gao, Peng; Wan, Qing; Deng, Fengjie; Wei, Yen; Zhang, Xiaoyong
Abstract : Aggregation‐induced emission (AIE) is an abnormal fluorescent phenomenon that has attracted great research interest in recent years. In particular, the fabrication and bioimaging applications of AIE‐active polymers have recently been intensively investigated. In this feature article, the recent advances and future prospects for the fabrication and biomedical applications of AIE‐dye‐based carbohydrate polymers are highlighted. Abstract : Aggregation‐induced emission (AIE) is an abnormal phenomenon that has sparked great attention for diverse applications in different fields. In particular, the fabrication and biological imaging applications of AIE‐active fluorescent organic nanoparticles (FONs) have become a focus in the emerging and promising fields. A large number of AIE‐active polymeric nanoprobes have recently been fabricated through different strategies. The advances and progress in this direction have also recently been summarized by some groups. However, the fabrication and biomedical applications of AIE‐active FONs based on carbohydrate polymers and AIE‐active dyes are quite rare and limited. In this feature article, the recently reported AIE‐active FONs with different structures and applications based on AIE‐active dyes and carbohydrate polymers are highlighted, and the major current limitations and development tendencies are also discussed.